Community participation in the development of GKJ Karangjoso as a religious tourist attraction - Bisma Caesario Kurniawan; I Putu Sudhyana Mecha; Auda Nuril Zazilah (Journal of Applied Sciences in Travel and Hospitality, 2022)
Java Island is one of the largest islands with many kinds of churches in it. However, most of them are not known to the public because of the low number of churches that are promoted as a religious tourist attractions. In addition, community participation in the development of religious tourism attractions is still minimal, this is indicated by the small number of people involved in the development of religious tourist attraction sites. The formulation of the problem from this research is to determine the kinds and level of community participation in the development of GKJ Karangjoso as a religious tourist attraction. The theory used in the research includes tourism, religious tourism attraction, community participation, data triangulation, and data reduction. This research method uses a qualitative descriptive method using the Miles & Huberman method with data reduction and data triangulation. The kinds of community participation found in GKJ Karangjoso is Get involved in organizational activities to mobilize other community participation. Meanwhile, the level of community participation found in GKJ Karangjoso is providing support. This research concludes that there is one form and one level of community participation in the development of GKJ Karangjoso as a religious tourism attraction.